Wildlife criminology - Nurse, Angus; Wyatt, Tanya, 1975- (Bristol : Bristol University Press, 2021)
The concept of wildlife criminology reaches new boundaries in this illuminating new study of exploitation of animals and its social implications. Reviewing harms like exploitation and trade, blood sports and wildlife as food, it considers the rights of animals as sentient beings and the impact of crimes on inter-human attitudes and violence.
Previously issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on January 8, 2021).
Keywords: Wildlife crimes; True Crime; Social services & welfare, criminology